Enzymology of RNA cap synthesis - Ghosh, Agnidipta (2010)
The 5′ guanine-N7 methyl cap is unique to cellular and viral messenger RNA (mRNA) and is the first co-transcriptional modification of mRNA. The mRNA cap plays a pivotal role in mRNA biogenesis and stability, and is essential for efficient splicing, mRNA export, and translation. Capping occurs by a series of three enzymatic reactions that results in formation of N7-methyl guanosine linked through a 5′-5′ inverted triphosphate bridge to the first nucleotide of a nascent transcript. Capping of cellular mRNA occurs co-transcriptionally and in vivo requires that the capping apparatus be physically associated with the RNA polymerase II elongation complex. Certain capped mRNAs undergo further methylation to generate distinct cap structures. Although mRNA capping is conserved among viruses and eukaryotes, some viruses have adopted strategies for capping mRNA that are distinct from the cellular mRNA capping pathway.